Pengaruh Intellectual Capital terhadap Kinerja Keuangan pada Bank Syariah di Malaysia Tahun 2019-2022 - Shara, Yuni; Kholis, Azizul; Ikhsan, Arfan (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to investigate the effect of Intellectual Capital on the financial performance of Islamic banks in Malaysia during the period 2019-2022. This research method uses a quantitative approach by collecting data from the annual financial statements of Islamic banks in Malaysia during the study period. Intellectual Capital is measured by Capital Employed Efficiency, Human Capital Efficiency and Structural Capital Efficiency. Financial performance is measured by ROA (Return on Assets). The data analysis technique uses Partial Least Square (PLS). The sample was selected based on purposive sampling and there were 13 Islamic Banks for 4 years. The results showed that intellectual capital has a positive and significant effect on financial performance. This finding indicates that the management and development of intellectual capital, such as efficient use of capital, improving employee skills, and strengthening organizational infrastructure, contribute positively to the financial performance of Islamic banks in Malaysia. The practical implication of this study is that the management of Islamic banks should pay special attention to the management of their intellectual capital as part of the strategy to improve ROA. Investment in intellectual capital development can generate long-term benefits for Islamic banks, especially in the face of intensifying competition in the banking industry.